(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This paper investigates the influence of a NCET on thermal performance and durability of S&T HE operating in corrosive media like that found in petroleum production. Traditional carbon-steel tubes corrode and erode, as well as foul up the process so that heat is not effectively transferred resulting in less efficiency, more frequently down time and costly servicing. This covers recent research on fibre-reinforced polymer and metal–matrix composite tubes for corrosion resistance, thermal conductivity, tensile strength and long-term stability when subjected to high temperature with pressure in a multiphase flow environment. A theoretical comparison of total heat-transfer coefficients, pressure drop and anticipated service life between composite and metallic tubes is generated. Consideration is given to design issues such as tube–sheet attachment, compatibility with current shell-and-tube layouts, and life-cycle cost effects. The outcomes should demonstrate the capability of suitably designed composite tubes to greatly improve performance and service life, while controlling corrosion failure. Guidelines for metallic and composite selection for petroleum heat exchangers are also presented, along with research needs for future experimental and industrial-scale work.